RANCANG BANGUN SISTEM NOMOR ANTRIAN SERVIS BERBASIS SMS GATEWAY - M. Khoirul Anam; Zulfikar Zulfikar; Agus Sifaunajah (Computer Society of Nahdlatul Ulama (CSNU) Indonesia, 2018)
Service queuing mechanism is now still using a manual system, where the consumer must come directly to the workshop and the consumer must queue up first. In need of a service queue service system that supports to overcome the old queue and for the workshop has certain characteristics of other workshops and Help improve the quality of service at the workshop. One type of technology implementation in terms of increasing business competition is to use the internet as a communications media owned by the company Application of a database that is as a container to accommodate the data processing queue service. This system uses the programming language PHP and MySQL.Aplikasi also provides SMS Gateway service to customers to minimize the occurrence of customer delays.This application also presents reports addressed to the owner (owner), namely: report queue number.Keywords: Service Queue, database, SMS Gateway PHP and MySQL.